IMPLEMENTATION OF STEM-BASED VOICED INTERACTIVE TORSO (TOBI) IN IPAS LEARNING AT MIN KUDUS - Eva Luthfi Fakhru Ahsani; Faza Dzulfikar Efendi (Indonesian Journal of Educational Development (IJED), 2025)
The lack of understanding of MIN Kudus students towards human digestive system IPAS learning is due to the media used that has not been able to present a concrete and detailed picture. This study aims to describe the implementation of STEM-based Voiced Interactive Torso (TOBI) in IPAS learning at MIN Kudus along with the responses of teachers and students. This research is included in descriptive qualitative research where the type of research is field research. Data will be obtained through observation, questionnaires, interviews, and documentation. Data analysis that will be carried out includes data reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of STEM-based Voiced Interactive Torso (TOBI) in IPAS learning at MIN Kudus can improve students' understanding of human digestive system material. This is evident in the activities of teachers with a percentage of 91% in the very good category and students with a percentage of 75% in the good category. While the results of teacher and student responses to design, relevance, attention, satisfaction, and confidence get a percentage of 85% and 81% including in the very good category.